(untitled) (Polis (Santiago), 2018)
Through an historical journey on the role of the state and civil society, the author posits that organizations and social movements in post-authoritarian state, due to the radical neo-liberal modernization and a political system of supervised democracy, there is no social space to have a political voice. The State accepts them, constrained to certain functions, but does not stimulate or favor their self-development. Given this, organizations must choose between submitting to this role, or seek self-development with all the difficulties and risks involved.